All together now: Disentangling semantics and pragmatics with together in child and adult language. (2nd April 2016) - Syrett, Kristen; Musolino, Julien
ABSTRACT: The way in which an event is packaged linguistically can be informative about the number of participants in the event and the nature of their participation. At times, however, a sentence is ambiguous, and pragmatic information weighs in to favor one interpretation over another. Whereas adults may readily know how to pick up on such cues to meaning, children—who are generally naïve to such pragmatic nuances—may diverge and access a broader range of interpretations or one disfavored by adults. A number of cases come to us from a now well-established body of research on scalar implicatures and scopal ambiguity. Here, we complement this previous work with a previously uninvestigated example of the semantic-pragmatic divide in language development arising from the interpretation of sentences with pluralities and together . Sentences such as Two boys lifted a block (together) allow for either a Collective or a Distributive interpretation (one pushing event vs. two spatiotemporally coordinated events). We show experimentally that children allow both interpretations in sentences with together, whereas adults rule out the Distributive interpretation without further contextual motivation. However, children appear to be guided by their semantics in the readings they access, since they do not allow readings that are semantically barred. We argue that they are unaware of the pragmatic information adults have at their fingertips, such as the conversational implicatures arising from the presence of a modifier, the probability of its occurrence being used to signal a particular interpretation among a set of alternatives, and knowledge of the possible lexical alternatives.